2009
DOI: 10.1093/jxb/erp365
|View full text |Cite
|
Sign up to set email alerts
|

Nicotiana tabacum agglutinin is active against Lepidopteran pest insects

Abstract: A jasmonate-inducible lectin called Nicotiana tabacum agglutinin or NICTABA was found in tobacco (Nicotiana tabacum cv Samsun) leaves. Since NICTABA expression is also induced after insect herbivory, a role in the defence response of tobacco was suggested. In this report, a detailed analysis was made of the entomotoxic properties of NICTABA using different transgenic approaches. First, purified NICTABA was shown to be strongly resistant to proteolytic degradation by enzymes present in the Lepidopteran midgut. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 54 publications
0
32
0
Order By: Relevance
“…measurable impact on digestive processes. A possible explanation is that chronically-ingested DVL tends to cluster with glycoproteins secreted in the midgut, forming a protein-lectin complex capable of interfering with enzyme recycling in the digestive system Vandenborre et al, 2010). Moreover, zymograms on native gels revealed that the activity of AGP5, a trypsin-like enzyme, was significantly decreased when midgut homogenates were incubated with DVL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…measurable impact on digestive processes. A possible explanation is that chronically-ingested DVL tends to cluster with glycoproteins secreted in the midgut, forming a protein-lectin complex capable of interfering with enzyme recycling in the digestive system Vandenborre et al, 2010). Moreover, zymograms on native gels revealed that the activity of AGP5, a trypsin-like enzyme, was significantly decreased when midgut homogenates were incubated with DVL (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nicotiana tabacum has several modes of action. It can be a nerve poison [27, 28], stomach poison, or repellent [29]. Baskaran and Narayanasamy [29] found N .…”
Section: Discussionmentioning
confidence: 99%
“…sinensis was toxic to Callosobruchus chinensis (L.) and Sitophilus oryzae (L.) (Coleoptera: Curculionidae), R. communis to Sitophilus zeamais Motsch (Coleoptera: Curculionidae), Ca. annuum, and N. tabacum to larvae of Lepidoptera , Vandenborre et al 2010, Ahn et al 2011. A. indica and Ar.…”
Section: Discussionmentioning
confidence: 99%